P86 Audit mapping against CQC Outcomes. (1st October 2013) - Stanford, Jo; Phillips, Ruth
Abstract : Audit mapping against CQC Outcomes Introduction: The Care Quality Commission (CQC) requires agencies to provide evidence that they are meeting the CQC outcomes. Clinical Governance is a framework through which organisations are accountable for continuously improving the quality of their services and safeguarding high standards of care. Aims: The Clinical Governance Reporting Guidelines have been reviewed and restructured inline with the Care Quality Commission (CQC) outcomes. The purpose of this exercise was to streamline the audit reporting process inline with the CQC, make the audits more meaningful, and avoid duplication of work. Methods: Using the hospices existing Clinical Governance Audit Programme, where possible, each CQC outcome was allocated to an audit. Some audits were allocated more than one 'outcome' Results: Below is an example of how some of the audits are mapped against the CQC Outcomes. Discussion: The children's hospice audit programme meets and provides evidence for many of the CQC Outcomes. Evidence for those the outcomes that are not met, can be provided in various other ways. Conclusion: This mapping exercise has been helpful in identifying how the hospice was already providing evidence for the CQC, but also helped to identify any shortfalls. Some audits have been reviewed to ensure that they serve a purpose and also can provide evidence for the CQC.